HF Test Current Injection-Based Self-Sensing Control of PMSM for Low- and Zero-Speed Range Using Two-Degree-of-Freedom Current Control - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (IEEE Transactions on Industry Applications, 2015)
This paper deals with an innovative self-sensing control scheme based on test current instead of voltage injection. Using two-degree-of-freedom current control, one can overcome the bandwidth limitations that made test current injection unattractive during the last 20 years. The two-degree-of-freedom control scheme consists of a model-based dynamic feedforward control to set the reference response and model reference tracking controllers providing disturbance rejection and position error signals for self-sensing control. Since two-degree-of-freedom control is a model-based control scheme, the compensation for secondary saliencies is inherently included in the precontrol. It is analytically shown that, in the case of alternating test current instead of voltage injection, just the precise knowledge, in general, of the current- and position-dependent secondary diagonal element of the inductance matrix is needed in the case of inductance saliency-based self-sensing control. The effectiveness of the proposed method is proven by experimental results.
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.LEEAS.hftest
Keywords: Current control; eddy currents; machine vector control; magnetic losses; motion control; permanent-magnet machines; permanent-magnet motors; saliency; self-sensing control; sensorless control; test current injection